Determinants of exchange rate in Malaysia / Nursuziana Fazira Abdul Wahab - Abdul Wahab, Nursuziana Fazira (Faculty of Business and Management, 2020)
This research attempts to investigate the relationship between the exchange rate and the independent variables, such as, inflation rate, interest rate, money supply, palm oil prices and trade in Malaysia. Secondary data was sourced within the period of January 2018 to December 2018. On the other hand, the technique that implemented to estimate the model was Multiple Linear Regressions and Granger causality test. The result from Multiple Linear Regressions showed that the determinants factors of exchange rate through interest rate, palm oil price and trade is capable of influencing which has an direct relationship and statistically significant to the exchange rate. However, inflation rate and money supply did not have any relationship with exchange rate. The conclusions for the studies show that interest rate, palm oil price and trade become the factors that affecting the exchange rate in Malaysia. From Granger causality test shows that inflation and exchange does not have causality relationship.